Detecting adulteration of stingless bee honey using untargeted 1H NMR metabolomics with chemometrics. (30th January 2022) - Yong, Chin-Hong; Muhammad, Syahidah Akmal; Aziz, Fatimatuzzahra' Abd; Nasir, Fatin Ilyani; Mustafa, Mohd Zulkifli; Ibrahim, Baharudin; Kelly, Simon D.; Cannavan, Andrew; Seow, Eng-Keng
Highlights: Detect stingless bee honey adulteration using 1 H NMR metabolomic with chemometrics. Preliminary 1 H NMR metabolomic fingerprints of authentic stingless bee honey. Preliminary 1 H NMR metabolomic fingerprints of adulterated stingless bee honey. Detect stingless bee honey adulterated with adulterants derived from C4 plants. Detect stingless bee honey adulterated with adulterants derived from C3 plants. Abstract: As stingless bee honey (SBH) is gaining in popularity in the Malaysian market, it is now prone to adulteration. The higher price of SBH compared to floral honey has led to the use of unusual adulterants such as vinegar and even floral honey to mimic the unique taste and appearance of SBH. Since the current AOAC 998.12 method fails to detect these adulterants as their δ 13 C values are in the range for C3 plants, untargeted 1 H NMR metabolomics was proposed. Principal component analysis of SBH 1 H NMR fingerprints was able to distinguish authentic SBHs from adulterated ones down to 1% adulteration level for selected adulterants. Discriminant analysis showed promising results in distinguishing the preliminary datasets of authentic SBHs from the adulterated ones, including discriminating SBHs adulterated with different adulterants derived from C3 and C4 plants. Hence, to assure any emerging adulterant can be detected, all 1 H NMR regions should be considered.